Shorter ovarian stimulation is detrimental to fresh embryo transfer outcomes in PCOS women undergoing GnRH antagonist protocol: a retrospective cohort study - Shan Xiao; Su Liu; Ling Hong; Zhiqiang Liu; Rui Jia; Hongzhan Zhang; Meilan Mo; TuRui Yang (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is a common endocrine disorder with dysfunctional ovulation affecting female fertility. The purpose of this study was to determine the association between gonadotropin (Gn) duration and in vitro fertilization (IVF) outcomes in PCOS women undergoing GnRH antagonist treatment. Retrospective cohort study at a large private fertility practice. Patients with PCOS undergoing the GnRHantagonist treatment between January 1, 2017, and July 31, 2021 were included. Patients were classified into two groups depending on their Gn duration, ≤ 8 days (n = 501) and >8 days (n = 1326). After propensity score matching (PSM), there were 87 PCOS women with Gn duration ≤ 8 days and 137 PCOS women with Gn duration >8 days in the fresh embryo transfer cycle. The primary outcomes measures included the clinical pregnancy, ongoing pregnancy, early miscarriage and live birth rate between the two groups after fresh embryo transfer. In addition, the embryo quality was also evaluated. There was no significant difference in baseline characteristics between groups. However, the total Gn dosage was lower in PCOS women in the ≤ 8 days group. In addition, the oocytes retrieved and D3 high quality embryos were compared between groups. However, the number of 2PN embryos was decreased in the group with Gn duration ≤ 8 days. The clinical pregnancy and live birth rate were significantly decreased in the ≤ 8 days group in fresh embryo transfer (52.87% vs. % 68.61%, 43.68% vs. 59.12%). After logistic regression, PCOS women with Gn duration ≤ 8 days were associated with poor clinical pregnancy and live birth rate. PCOS women with shorter Gn duration (≤ 8 days) were not associated with impaired embryo outcomes except for 2PN embryos in GnRH antagonist protocol. However, the shorter Gn stimulation was detrimental to clinical pregnancy outcomes in fresh embryo transfer cycle.